2015
DOI: 10.1002/pros.23058
|View full text |Cite
|
Sign up to set email alerts
|

Expression of IL-17A, E, and F and their receptors in human prostatic cancer: Comparison with benign prostatic hyperplasia

Abstract: Our data are compatible with hypothesis that IL-17A acting through IL-17RA, but not IL-17CR contribute to the pathogenesis of BPH and PCa. In contrast, IL-17E interacting with the IL-17BR might have an anti-tumor effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 34 publications
0
24
1
Order By: Relevance
“…IL-17F has been characterized in different cancer entities. For example, IL-17F is significantly elevated in prostate cancer and triggers increased NF-κB signaling in B and T cells in patients with chronic lymphocytic leukemia [5, 6]. However, the roles of IL-17B, IL-17C, and IL-17D in cancer are less defined.…”
Section: Introductionmentioning
confidence: 99%
“…IL-17F has been characterized in different cancer entities. For example, IL-17F is significantly elevated in prostate cancer and triggers increased NF-κB signaling in B and T cells in patients with chronic lymphocytic leukemia [5, 6]. However, the roles of IL-17B, IL-17C, and IL-17D in cancer are less defined.…”
Section: Introductionmentioning
confidence: 99%
“…Our experimental data from BPH and PC tissue according to (TRAF‐6+, ASK‐1+, Raf‐1+) and (TRAF‐6+, ASK‐1+, Raf‐1−) subgroups showed that ASK‐1/MEK‐6/p38 was expressed higher in BPH than PC. Our previous studies have demonstrated the high expression of pro‐inflammatory cytokines by prostate epithelial cells [10] and several reports have shown that IL‐17 was also expressed by these cells [30]. Therefore, these findings support the hypothesis that prostate epithelial cells could initiate immune responses and inflammation under physiological and pathological conditions.…”
Section: Discussionmentioning
confidence: 69%
“…All the tissue slides were stained with a similar protocol as previously described [16]. Antigen retrieval was realized under high temperature and high pressure with sodium citrate solution (PH=6).…”
Section: Immunohistochemistrymentioning
confidence: 99%